Automobilių transporto raida Klaipėdos krašte XX amžiaus pirmoje pusėje (1900-1939) - Žukas, Julius (Lietuvos istorijos studijos, 2009)
The first car in Klaipėda District (Memelgebiet) appeared in 1900, while motor transport started to spread from the 3rd decade of the XX century. In the beginning of 1920, there were 49 cars registered in the district, in 1922, 108 cars registered, while by the end of 1928 - 307 cars registered. The most popular were passenger cars, whereas buses were the latest to appear and the least widespread. At the end of 1937, there were 390 passenger cars, 99 trucks, and 40 buses registered in the district. Most of the cars were registered in Klaipėda city. Compared to the Lithuanian Republic, the degree of motor transport prevalence in Klaipėda district was greater: in 1938 there were 903 residents per one car in Lithuania and 222 residents per one car in the Klaipėda district. In Klaipėda district, the most widespread were German and American cars, popular makes being Opel, Ford, Chevrolet, and Mercedes Benz. From the 4th decade of the XX century, passenger motor transport started to develop rapidly in Klaipėda district. In 1930, there were 13 interurban bus service routes operating, transporting 166,870 passengers, whereas in 1937 - 23 routes and 397,537 passengers transported. Most of the routes were operated by one bus; an exception was resort routes Klaipėda - Palanga and Klaipėda - Giruliai during the summer season. Starting from the middle of the 4th decade, post buses began to dominate in interurban bus services. In 1938, post administration had 18 buses. From 1934, passenger bus transport was functioning in Klaipėda city with 12 buses running on four routes. In 1935, city buses (exploited by a company belonging to Klaipėda municipality) transported 1,364 million passengers, in 1936 - 1,519 million, in 1937 - 1,752 million passengers. Most of the passengers were transported by the first route uniting Klaipėda railway station and the industrial Smeltė (Schmelz) suburb. Car exploitation and traffic rules in Klaipėda district were strictly regulated; the main normative acts were prepared in the 4th decade of the XX century. A person needed to receive permission to use a vehicle, and such permission had to be extended annually. Car owners were also obligated to pay an annual fee, which was calculated for passenger cars according to engine power, and for trucks and buses - according to weight. Only persons with a driver’s license who completed an officially accredited driving school could drive a car. According to a decree dated 1933, the organization order of passenger motor transport was also regulated in detail. Based on decrees of the district’s authority, people were punished for violation of traffic rules (exceeding the speed limit, driving drunk, using a car without permission extended, etc.), and the most frequent penalty applied was monetary fines. In autumn 1938, motorized transport police was established in Klaipėda district for traffic supervision.